A comparative evaluation of analgesic effects of using intravenous paracetamol versus intravenous diclofenac post-operatively in laparoscopic cholecystectomy patients in SMIH, department of surgery, Dehradun - Bijalwan, Anurag; Singhal, Pradeep; Altamash, Syed (International Surgery Journal, 2019)
Background: Post-operative adequate analgesia plays an important role in early mobilization, short hospital stay and patient satisfaction in laparoscopic cholecystectomy. The use of opioids for providing postoperative analgesia has been marked by side effects like vomiting, nausea, sedation, respiratory distress, etc. hence, alternate drugs like paracetamol (PCM) and diclofenac are commonly used. In this study, we have compared the analgesic efficacy and any associated side effects of the two commonly used non-opioid NSAIDS namely paracetamol and diclofenac. Methods: We compared 50 patients undergoing laparoscopic cholecystectomy in ASA I and II. They were randomly divided into two groups, Group A and Group B. Group A was administered intravenous PCM and Group B was administered injection diclofenac sodium. Postoperatively, these patients were assessed for pain, blood pressure, respiratory rate, and presence of any side effects like nausea, vomiting or any respiratory discomfort. Results: The mean DBP, MAP and VAS score was significantly (p-value <0.05) in Group A as compared to Group B patients at 4, 8, 12 and 24 hours postoperatively. There was no statistically significant difference in mean SBP and O2 saturation in both groups. The mean pulse rate was lower in Group A as compared to Group B at 8, 12 and 24 hours. Conclusions: This study concluded that postoperative PCM infusion provided better analgesia for a prolonged period of time with minimal side effects.